Diamond Raman laser: a promising high-beam-quality and low-thermal-effect laser. (5th July 2021) - Li, Yulan; Ding, Jie; Bai, Zhenxu; Yang, Xuezong; Li, Yuqi; Tang, Jingling; Zhang, Yu; Qi, Yaoyao; Wang, Yulei; Lu, Zhiwei
Abstract: Stimulated Raman-scattering-based lasers provide an effective way to achieve wavelength conversion. However, thermally induced beam degradation is a notorious obstacle to power scaling and it also limits the applicable range where high output beam quality is needed. Considerable research efforts have been devoted to developing Raman materials, with diamond being a promising candidate to acquire wavelength-versatile, high-power, and high-quality output beam owing to its excellent thermal properties, high Raman gain coefficient, and wide transmission range. The diamond Raman resonator is usually designed as an external-cavity pumped structure, which can easily eliminate the negative thermal effects of intracavity laser crystals. Diamond Raman converters also provide an approach to improve the beam quality owing to the Raman cleanup effect. This review outlines the research status of diamond Raman lasers, including beam quality optimization, Raman conversion, thermal effects, and prospects for future development directions.